PENGUATAN PENANAMAN PENDIDIKAN POLITIK BAGI KADER MUDA PERGUNU KEDIRI - Binti Suaidah Hanur; Izzatus Sholihah; Laili Hanifah; Lissa Nuril Fauziah; Ida Kurnia Wahdati; Zahratun Nafi'ah Raikhatul Janah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
Being a good citizen and being able to behave in accordance with the socio-cultural norms prevailing in society is an example of someone who carries out developmental tasks in young adulthood well. Then what if someone unable to become a responsible citizen and is also unable to adapt to the socio-cultural environment that applies in the community where the person lives. The goal of this PKM exercise is to empower PERGUNU Kediri members to grow in their social and personal lives within their living environment. Participatory Action Research (PAR), in which the instructor is directly involved in the service provided, is the methodology employed in this coaching activity. The outcomes of the PKM's implementation show that the political education strengthening activity increases a sense of responsibility as a good citizen, Additionally, PERGUNU's participation in its social activities helps to solidify the feeling of nationalism, which benefits this electoral activity.